2008
DOI: 10.1007/s00296-008-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity prevents bone loss in premenopausal women with rheumatoid arthritis: a cohort study

Abstract: The aim of the study was to compare the bone loss and the influence of physical activity between premenopausal women with rheumatoid arthritis (RA) and healthy women. A total of 71 patients with RA and 29 healthy premenopausal women with the criteria of the American College of Rheumatology for RA were followed for 2 years. Of these 85% were Caucasian, aged 38 +/- 6.6 years and with a duration of disease of 88 +/- 50 months and 48 (71.8%) used GC, mean daily dose, 7.3 +/- 3.5 mg. There was a reduction in the T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
0
28
1
Order By: Relevance
“…Greene et al 42 and Raftery et al 43 used patient populations as controls, and Lemmey et al 38 used both patient and healthy population controls while the remainder used solely healthy populations. Three 39,40,44 of the four studies which completed a follow up of subjects, were able to complete follow up of all subjects or maintain numbers lost to less than 20%. In addition, only 2 studies 39,45 clearly demonstrated that the sample included was truly representative of the average patient with RA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greene et al 42 and Raftery et al 43 used patient populations as controls, and Lemmey et al 38 used both patient and healthy population controls while the remainder used solely healthy populations. Three 39,40,44 of the four studies which completed a follow up of subjects, were able to complete follow up of all subjects or maintain numbers lost to less than 20%. In addition, only 2 studies 39,45 clearly demonstrated that the sample included was truly representative of the average patient with RA.…”
Section: Resultsmentioning
confidence: 99%
“…They include kJ/day, 10 hrs/week, 49 hrs/day, 42 mins/ day, 42,49 MJ/day, 47 kcals/week, 41 mins/week, 45,50 kcals/ day, 48 METmin per week 51 and METhours/day, 52 as well as exercise level, 38 physical activity level, 47 sum score of outcome measure, 44,46 meeting of national recommendations, 50 daily average number of steps, 48 number of steps taken, 43 vigor of steps, 43 time spent standing, 43 total energy in arbitrary units, 43 participation in activity domains, 39 and % in different physical activity categories. 40 …”
Section: Resultsmentioning
confidence: 99%
“…A prospective cohort study in RA with 72% of patients on GC therapy showed that moderate physical activity reduced the risk of osteopenia 83. Moreover, a cross-sectional study in RA with most patients on GCs showed a positive association between quadriceps muscle strength and femoral neck bone mineral density (BMD) 84…”
Section: Recommendationsmentioning
confidence: 99%
“…With specific reference to RA, a sedentary lifestyle confers a relative risk of 1.6 for low BMD in RA patients, and even moderate physical activity has been shown to reduce this risk by 50% (Tourinho et al, 2008). Additionally, de Jong et al (2004) showed that bone loss at the hip was reduced in RA patients participating in the 2 year, high-intensity RAPIT exercise program (median -1.1% vs -1.9% for nonexercising controls, p<0.05).…”
Section: Effects On Bonementioning
confidence: 99%